DAYA TARIK PENGEMBANGAN DESA WISATA RANTAU BAIS KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR PROVINSI RIAU - Yuni Rahma Ayu; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
A tourist attraction is anything that has a uniqueness, beauty, and value in the form of a diversity of natural, cultural, and man-made diversity that is the target or destination of tourist visits. Attraction can attract tourists to visit tourist attractions and must meet the requirements are (1) what to see, (2) what to do, (3) what to buy, (4) what to arrived (5) what to stay. (1) This study aims to find out and analyze the attractiveness in the development of Rantau Bais Tourism Village, Tanah Putih District, Rokan Hilir Regency, Riau Province. (2) Knowing and analyzing external factors that support and hinder the development of tourism in the Rantau Bais Tourism Village, Tanah Putih District, Rokan Hilir Regency, Riau Province. This study uses a qualitative method using a descriptive approach, the subject of this study is the Head of the Rantau Bais Village, Chairperson of Pokdarwis, and Community Leaders. Data collection techniques carried out by observation, interviews, and documentation. Analysis of the data used in conducting this research is data reduction data, data presentation, and making conclusions. The results of this study indicate that this Rantau Bais tourism village has natural tourist attraction, cultural tourism attraction, and special interest tourist attraction. The natural attraction is the flora and fauna of Tilan Island and the Rokan River. The cultural appeal of the breeders' culture, the culture of the fishing communities in the Rokan river, and the culture of the indigenous people. The conclusion of this research is to maximize the attractiveness of the development of attractions in the Village of Rantau Bais, by adding attractions to attract tourists who come to the village, as well as repairing and equipping infrastructure facilities together with local travelers. Keywords: Attraction, Tourist Attraction, Tourist Village